STRATEGI PEMASARAN JASA PENDIDIKAN MAS ALIYAH NO.21 KAMPIRI (KAB WAJO) - Mastati; Habibah, Sitti; Basri, Syamsurijal (Irfani, 2026)
This study examines the implementation of marketing strategies for educational services at MAS As'adiyah No. 21 Kampiri, Wajo district with a 7P (Product, Price, Place, Promotion, Person, Physical Evidence, and Process) marketing mix approach. The focus of this research is a qualitative approach and a type of descriptive research. The data collection procedures used are interviews, observations and documentation. Checking the validity of the data using the triangulation method, data analysis is carried out by data reduction, data presentation to conclusion drawn. The data sources in this study are the Principal and Deputy Head of Curriculum. The results of the study show that (1) Marketing Strategy for MAS As'adiyah Education Services No. 21 Kampiri, namely (a) Product: the madrasah has uploaded achievements on social media (b) Price: the madrasah implements free education without registration fees and monthly tuition as the main attraction, (c) Place, the location of the madrasah is strategic and easy to reach (d) Promotion, carried out through social media, distribution of brochures,  visits to other schools, and formal cooperation with universities, (e) Person, madrasah uses teacher testimonials as a marketing strategy (f) Process, madrasah routinely holds meetings with stakeholders for program evaluation, (2) Supporting Factors & Inhibitions (a) Supporting Factors: government support and commitment of school residents, (b) Inhibiting Factors: barriers include limited infrastructure, human resources, and public perception of madrasah education